Pengaruh Mutu Produk, Persepsi Harga Dan Variasi Produk Terhadap Keputusan Pembelian Konsumen (Studi Kasus Pada Toko Serba 45.000 Ditenggarong) - Hapsari, Winda; Palinggi, Yonathan; Idham, Idham (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2021)
Abstract: The purpose of this study was to determine the effect of product quality and price perception partially or simultaneously on consumer perceptions at 45,000 Convenience Stores in Tenggarong and to determine the dominant variables in influencing consumer perceptions between the two independent variables. The analytical tool used in this research is multiple regression method with the help of SPSS 20.0 For Window's, with a population of 150 respondents and a sample of 70 respondents. Based on the results of the study, it can be concluded that the variables of product quality, price perception and product variations simultaneously affect consumer purchasing decisions. Product quality variable has a partial effect on consumer purchasing decisions at 45,000 Convenience Stores in Tenggarong. Price perception variable (X2) partially influences consumer purchasing decisions at 45,000 Convenience Stores in Tenggarong, Product variation variable (X3) partially affects consumer purchasing decisions at 45,000 Convenience Stores in Tenggarong. From the three partial correlation test results, it can be seen that the value of the product quality variable has the greatest influence compared to the price perception variable and product variation, so that the product quality variable is the most dominant variable influencing consumer purchasing decisions. Keywords: Product Quality, Price Perception, Product Variation, Purchase Decision